A Two-Stage Wind Grid Inverter with Boost Converter - Yanbo Che; Wen Zhang; Leijiao Ge; Jijie Zhang (Journal of Applied Mathematics)
At present, the conversion efficiency of commercial small wind grid inverter is low, and, in case of low wind speed, the wind energy cannot be used efficiently. In order to resolve this problem, it is necessary to improve the topological structure and control strategy, and design a new small wind grid inverter. In this paper, we apply a two-voltage stage topology with boost converter. The boost circuit is to achieve the maximum power output of the wind energy by the segmented regulation, while the improved inverter topology realizes the overall system function with the former stage circuit. The experimental results show that the new wind grid inverter has superior performance in the low wind speed, and has the high quality energy output. This research has an important practical significance to improve the utilization of renewable energy.